GEREJA SEBAGAI PERSEKUTUAN PERSAHABATAN YANG TERBUKA MENURUT JÜRGEN MOLTMANN - Yohanes Krismantyo Susanta (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2020)
Using a qualitative descriptive approach, this article shows that according to Moltmann, the church concept of fellowship or Koinonia is too often based on uniformity. Against the Koinonia model, Moltmann raised the biblical concept of the importance of strangers, travellers, outcasts, and sinners. According to Moltmann, the church cannot be a boat of sameness in navigating the ocean of diversity. Therefore, Moltmann offers the concept of a trinitarian partnership based on friendship. For Moltmann, the good news about Koinonia from the Triune God is not marked by friendship in uniformity but by a bond that unites, respects, and embraces differences. True Koinonia means more than just accepting and embracing tension and conflict. True Koinonia is about accepting and embracing each other (and God). The ultimate sign of true Koinonia is friendship. Moltmann emphasized the church's call to be an open fellowship of friendship by promoting freedom, equality, and love. Moltmann, at the same time, put forward a criticism of the church structure, which - in Moltmann's terms - was built on the principle of monotheistic hierarchy, which was loaded with oppression.